Kluyveromyces osmophilus is not a synonym of Zygosaccharomyces mellis; reinstatement as Zygosaccharomyces osmophilus comb. nov. Issue 5 (29th April 2020) - Matos, Thelma T. S.; Teixeira, Juliana F.; Macías, Laura G.; Santos, Ana Raquel O.; Suh, Sung-Oui; Barrio, Eladio; Lachance, Marc-André; Rosa, Carlos A.
Abstract : Kluyveromyces osmophilus, a single-strain species isolated from Mozambique sugar, has been treated a synonym of Zygosaccharomyces mellis . Analyses of D1/D2 LSU rRNA gene sequences confirmed that the species belongs to the genus Zygosaccharomyces but showed it to be distinct from strains of Z. mellis . During studies of yeasts associated with stingless bees in Brazil, nine additional isolates of the species were obtained from unripe and ripe honey and pollen of Scaptotrigona cfr. bipunctata, as well as ripe honey of Tetragonisca angustula . The D1/D2 sequences of the Brazilian isolates were identical to those of the type strain of K. osmophilus CBS 5499 (=ATCC 22027), indicating that they represent the same species. Phylogenomic analyses using 4038 orthologous genes support the reinstatement of K. osmophilus as a member of the genus Zygosaccharomyces . We, therefore, propose the name Zygosaccharomyces osmophilus comb. nov. (lectotype ATCC 22027; MycoBank no. MB 833739).